Declarative Speech Act as Form of Regulation in Russian Penitentiary Law of the Early 19th Century - L. M. Golikov (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article is devoted to the description of speech forms of expression of legal norms in the penitentiary law of the first quarter of the 19th century. The source of research is the Charter on exiles of 1822 - the normative act that served as the certain sample for criminally-executive law of Russia in the pre-revolutionary period. The relevance of the work is seen in the fact that it will allow to present the laws of the construction of legal norms in modern law-making practice more fully. The novelty of research lies in the implementation of the historical approach when considering declarations as speech acts, which implement the defining text-forming category of legislative genres-directives most specifically. The author notes that such regulatory speech forms are productive for the language of law. On the material of legal discourse of the beginning of the 19th century the article highlights the types of regulatory declarations (declarations expressed explicitly, and declarations in the form of descriptive statement; the latter include the definitive descriptions and descriptions of situations). The author defines their semantic-syntactic structure, presents classifying features of speech act, among which the conventionality and institutionality; identity of the expressed propositional content of legal reality; performativity and non-descriptiveness; ability to realize a directive perlocutive effect are considered relevant.